Flexible with the truth? Exploring the relationship between labour market flexibility and labour market performance. A report for the TUC - Reed, Howard (Colchester, 2010)
"This report looks in detail at the relationship between labour market flexibility (LMF) and economic performance. It is designed to inform the TUC ToUChstone pamphlet Will labour market regulation prevent economic recovery? Between the early 1980s and the mid-1990s, the orthodox policy stance known as "neoliberalism" became the dominant policy view in most developed economies. The OECD's 1994 Jobs Study was typical of this approach, stressing the role of LMF as an essential precondition of economic success for developed economies. But since the late 1990s there has been a partial retreat from neoliberal orthodoxy, as a growing body of research suggested that the idea that there was some simple positive relationship between the flexibility of a country's labour market and its economic performance was simply not supported by the empirical evidence. One might have thought that the implosion of global credit markets and the ensuing economic crisis would drive the final nail into the coffin of the orthodox economic prescription for success, but paradoxically the crisis has presented an opportunity for supporters of labour market deregulation to make a comeback. Neoliberal commentators argue that highly regulated labour markets perform reasonably well during boom periods but cannot cope with recessions - and that therefore the UK and other developed economies need to deregulate their labour markets to ensure a strong economic recovery (even though the UK already has one of the most deregulated labour markets in the developed world). The aim of this report is to respond to the proponents of further deregulation by asking firstly whether there is any relationship between LMF and economic performance; and secondly, if there is a relationship, does more regulation mean worse economic performance? Or can increased regulation improve economic performance in some circumstances?"